Kajian Jarak Legowo Terhadap Iklim Mikro pada Budidaya Padi Sistem Jajar Legowo - I Putu Hendra; S - Sumiyati; I Wayan Tika (Program Studi Teknik Pertanian, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2014)
This study was conducted to determine the legowo distance studies in rice farming systems legowo row. This study is also expected to get the optimal distance legowo on legowo row planting system to improve the productivity of rice in Subak system. This research is divided into 5 treatment, the treatment in accordance with local farmers distance of 28 cm ; legowo 6:1 with wide legowo 1.25 x 28 cm ; legowo 6:1 with wide legowo 1.50x28 cm ; legowo 6:1 with wide legowo 1.75 x 28 cm ; legowo 6:1 with wide legowo 2 x 28 cm. This study was repeated 3 times. Parameters observed in this study ware : microclimate include: ambient temperature. The results suggest the application of legowo 6:1 cropping systems with a wide range legewo difference in each treatment shown to affect the relative humidity.